2009
DOI: 10.1016/j.jchromb.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic studies of partitioning behavior of lysozyme and conalbumin in aqueous two-phase systems

Abstract: The objective of this study was to determine the thermodynamic parameters (Delta(tr)G, Delta(tr)H and Delta(tr)S) associated with lysozyme and conalbumin partitioning in aqueous two-phases systems (ATPS). Influence of salt type and polyethylene glycol (PEG) concentrations on the partition coefficient of lysozyme and conalbumin from egg white was studied. The evaluated ATPS were composed of PEG 1500 and inorganic salts (sodium citrate and sodium sulfate) at a temperature of 25 degrees C and pH 7.0, with PEG 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 11 publications
2
20
0
1
Order By: Relevance
“…Egg white proteins are considered model of choice for studying proteins because of their high nutritional and biological value [9]. Conalbumin (CA), one of the main ironbinding monomeric glycoproteins containing D-mannose and D-galactose sugar moiety, is present in egg white.…”
Section: Introductionmentioning
confidence: 99%
“…Egg white proteins are considered model of choice for studying proteins because of their high nutritional and biological value [9]. Conalbumin (CA), one of the main ironbinding monomeric glycoproteins containing D-mannose and D-galactose sugar moiety, is present in egg white.…”
Section: Introductionmentioning
confidence: 99%
“…A casca do ovo é fonte de cálcio e substituto do carbonato de cálcio, que são produtos amplamente utilizados pelas indústrias alimentícias, farmacêuticas, odontológicas e de cosméticos (NAVES et al, 2007). A clara do ovo é fonte de lisozima e conalbumina, que são proteínas de alto valor nutricional e funcional (SOUSA et al, 2009). A albumina usada em suplementos alimentares controla a hipertensão e o ganho de massa muscular (SALVADOR & SANTA, 2002).…”
Section: Introductionunclassified
“…Coimbra et al [22] observed that ␤-lactoglobulin partitioned almost quantitatively between the two phases while ␣-lactalbumin was enriched in the top-phase, in ATPS containing PEGs and potassium phosphate. With the egg white proteins lysozyme and conalbumin Sousa et al [33] found, using ATPS formed by PEG 1500 and sodium salts (sodium citrate and sodium sulfate), that lysozyme tends to concentrate in the polymer-rich phase while conalbumin concentrates in the salt-rich phase.…”
Section: Partitioning Results For Peg 1500/sodium Phosphate Atpsmentioning
confidence: 99%
“…On the contrary, with the increase of TLL, the transfer of the biomolecules will tend toward one of the two phases, i.e., the values of K become increasingly distant from 1. This behavior results from the difference in composition between the phases, which engenders changes of entropic and enthalpic effects on the affinity of a given biomolecule toward each phase [32,33]. In that way, the phase composition, expressed by the TLL of the studied systems, can influence the partitioning behavior: an increasing of the TLL is likely to favor the partitioning of the casein hydrolysates.…”
Section: Equilibrium Datamentioning
confidence: 99%